An inverse problem on determining upto first order perturbations of a fourth order operator with partial boundary data. (24th September 2015) - Ghosh, Tuhin
Abstract: Here we consider the following perturbed fourth order elliptic differential operator with the Dirichlet boundary condition in a bounded domain ( ) with smooth boundary. We find that can be determined uniquely by measuring the Dirichlet-to-Neumann map on partial boundary of the domain, where the partial boundary is governed by linear-weight function.